2020
DOI: 10.1186/s12991-020-00275-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with depression among pregnant mothers in the West Shoa zone, Ethiopia: a community-based cross-sectional study

Abstract: Background: Depression during pregnancy, the most prevalent mental health problem, can alter fetal development and has important consequences on the offspring's physical and mental health. Evidence suggests increasing rates of prevalence of depression in low-income settings such as Ethiopia. However, there are a few studies on the topic with inconsistent results. Therefore, the aim of this study was to investigate the prevalence of antenatal depression and its correlates among pregnant women in Ethiopia. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
2
10
2
Order By: Relevance
“…Kubota et al (29) found that around 6.5% of women reported depression during pregnancy, whereas 11.2% of them experienced depression at 1 month postpartum using the EPDS. Based on the PHQ-9, Bitew et al (31) reported that the prevalence of depression in antenatal women was 28.70%, whereas Tiki et al (32) found that 32.3% of the women experienced depression during pregnancy. However, caution should be taken in direct comparisons because of the use of different measurement instruments, sampling methods, and sociodemographic characteristics between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Kubota et al (29) found that around 6.5% of women reported depression during pregnancy, whereas 11.2% of them experienced depression at 1 month postpartum using the EPDS. Based on the PHQ-9, Bitew et al (31) reported that the prevalence of depression in antenatal women was 28.70%, whereas Tiki et al (32) found that 32.3% of the women experienced depression during pregnancy. However, caution should be taken in direct comparisons because of the use of different measurement instruments, sampling methods, and sociodemographic characteristics between studies.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, the prevalence estimates of antenatal depression ranges from 6.8 to 32.3% [17][18][19][20][21][22], by using Edinburgh Postnatal Depression Scale (EPDS) with the cutoff point of ≥13.…”
Section: Introductionmentioning
confidence: 99%
“…The average duration between data collection and publication was 2,018.187 ± 1.709 in the studies included in the analysis. The studies were conducted in Israel (Adler et al, 2019), United States (Gildner et al, 2020; Kalmbach et al, 2019; Kinser et al, 2018; Perzow et al, 2021), Turkey (Akgor et al, 2021; Alan et al, 2020; Nacar & Taşhan, 2019; Sel et al, 2019), Ethiopia (Bante et al, 2021; Belay et al, 2018; Duko et al, 2019; Gebremichael et al, 2018; Habtamu Belete et al, 2019; Shitu Ayen et al, 2020; Tesfaye & Agenagnew, 2021; Tiki et al, 2020), Bangladesh (Begum & Biswas, 2020), Italy (Cena et al, 2020; Ravaldi & Vannacci, 2020), China (Dong et al, 2021; Lau et al, 2018; Lin et al, 2021; Mo et al, 2018; Yang et al, 2021; Yu et al, 2020; Zhang et al, 2021; Zhang, Yang, et al, 2020), Denmark (Ertmann et al, 2020), South Africa (Govender et al, 2020; Kaiyo-Utete et al, 2020), Iran (Hamzehgardeshi et al, 2021; Kazemi & Dadkhah, 2022; Saadati et al, 2021), Finland (Laitinen et al, 2021), Ghana (Lillie et al, 2020), Vietnam (Luong-Thanh et al, 2021), Croatia (Mikšić et al, 2018), Malez either (Nasreen et al, 2018), India (Sheeba et al, 2019; Venkatesh et al, 2019), Pakistan (Sabir et al, 2019; Shahid et al, 2020), Poland (Smyka et al, 2020; Stepowicz et al, 2020), Thailand (Tuksanawes et al, 2020), and the Netherlands (Zilver et al, 202...…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies that were included in this systematic review and meta-analysis reported findings about the prevalence of depression symptoms during pregnancy (Adler et al, 2019; Bante et al, 2021; Begum & Biswas, 2020; Belay et al, 2018; Dong et al, 2021; Duko et al, 2019; Gebremichael et al, 2018; Govender et al, 2020; Habtamu Belete et al, 2018; Hamzehgardeshi et al, 2021; Kaiyo-Utete et al, 2020; Kinser et al, 2018; Lau et al, 2018; Lillie et al, 2020; Lin et al, 2021; Mikšić et al, 2018; Mo et al, 2018; Nacar & Taşhan, 2019; Nasreen et al, 2018; Sabir et al, 2019; Shahid et al, 2020; Sheeba et al, 2019; Shitu Ayen et al, 2020; Tesfaye & Agenagnew, 2021; Tiki et al, 2020; Tuksanawes et al, 2020; Yang et al, 2021; Yu et al, 2020; Zhang, Wang, et al, 2020; Zhang, Yang, et al, 2020). The combined results of these studies indicated that the estimated depression symptoms rate was 22.6% (95% CI: 0.176–0.346; z : −4.722, p < .001, I 2 : 99.673).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation